Compostos fenólicos e atividade antimicobacteriana das folhas de Ficus benjamina L. e Ficus luschnathiana (Miq.) Miq. - Cruz, Ritiel Corrêa da (2011)
The following work presents an evaluation of the antimycobacterial activity (against Mycobacterium smegmatis) of the extracts, fractions and some phenolic compounds present in the leaves of Ficus benjamina L. and Ficus luschnathiana (Miq.) Miq., along with an estimation of the total phenolic content and the quantification of some of these compounds by High Performance Liquid Chromatography (HPLC). The phenolic estimation (Folin-Ciocalteu method) revealed that the crude extracts and the high polarity fractions from these extracts (ethyl acetate and n-butanol) are rich in polyphenols, although, its amount are not directly related to the antimycobacterial activity. The evaluation of this biological activity was performed by broth microdilution method, furnishing the minimum inhibitory concentration (MIC) of the extracts, fractions and tested compounds. The better biological activity was verified with butanolic fraction from F. luschnathiana (MIC = 156,25 μg/mL) and ethyl acetate fraction from F. benjamina (MIC = 312,50 μg/mL). However, the correlation of these good results with specific compounds was not possible, since technical difficulties prevented the isolation of substances from these fractions; and concerning the screened polyphenols only quercetin was encountered in butanolic fraction. In addition, quercetin exerted weak antimycobacterial activity against M. smegmatis (MIC = 625,00 μg/mL), much weaker than that observed for the fraction. The other investigated standards that were encountered in the extracts and fractions (caffeic and chlorogenic acids, rutin and kaempferol), also exhibited weak inhibitory effect. Thus, the good antimycobacterial activity observed for the fractions above mentioned are probably not related to these phenolics, still it may be related to compounds of the same nature. Many polyphenols, such as flavonoids, have been reported as mycobacterial growth inhibitors, thus it is also possible to conclude that the structural characteristics of quercetin, rutin and kaempferol do not support the biological activity studied.